2017
DOI: 10.3233/cbm-170670
|View full text |Cite
|
Sign up to set email alerts
|

MiR-186 inhibits proliferation, migration, and invasion of non-small cell lung cancer cells by downregulating Yin Yang 1

Abstract: Our results suggest that miR-186 and its target gene (YY1) could possibly serve as new prognostic biomarkers and therapeutic targets for treating NSCLC in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…Accordingly, the upregulation of TM4SF1-AS1 identified in our recurrent samples may result in the overexpression of STEAP2 and possible lower expression of miR-186 in OvCa. is theory was validated in our study and previous studies: extensive evidence had suggested that miR-186 was a tumor suppressor gene, with a downregulated expression level in cancer tissues, cells [30,31], and blood of recurrent oral squamous cell carcinoma patients compared with controls [32], including OvCa [33]. Overexpression of miR-186 into cancer cells significantly inhibited proliferation, invasion, metastasis [29,34,35], and induced mesenchymal-to-epithelial transition, G1 cell cycle arrest, and cell apoptosis [33].…”
Section: Discussionsupporting
confidence: 80%
“…Accordingly, the upregulation of TM4SF1-AS1 identified in our recurrent samples may result in the overexpression of STEAP2 and possible lower expression of miR-186 in OvCa. is theory was validated in our study and previous studies: extensive evidence had suggested that miR-186 was a tumor suppressor gene, with a downregulated expression level in cancer tissues, cells [30,31], and blood of recurrent oral squamous cell carcinoma patients compared with controls [32], including OvCa [33]. Overexpression of miR-186 into cancer cells significantly inhibited proliferation, invasion, metastasis [29,34,35], and induced mesenchymal-to-epithelial transition, G1 cell cycle arrest, and cell apoptosis [33].…”
Section: Discussionsupporting
confidence: 80%
“…Feng et al confirmed miR-186 significantly upregulated in lung adenocarcinoma samples and cells, in comparison with the adjacent noncancerous samples and normal lung epithelial cells BEAS-IB (13). However, several groups reported that the levels of miR-186 were markedly decreased in NSCLC samples and cells (14)(15)(16)(17)(18)(19)(20). Prostate cancer is the most common non-skin cancer in males, with there being ∼1.6 million cases worldwide annually (60).…”
Section: Altered Expressions Of Mir-186 In Different Cancersmentioning
confidence: 99%
“…In the five types of controversial cancers, there were many reports that miR-186 served as a tumor suppressor miRNA by target multiple oncogenes, which was contradictory to the previous statements. In NSCLS, miR-186 inhibited cell proliferation by targeting CCND1 (coding cyclins D1), CDK2, CDK6 (14), CDK1 (20), SIRT6 (15), and ROCK1 (16), inhibited migration and invasion via targeting ROCK1 (16), MAP3K2 (17), YY1 (18), and Cdc42 (19), and induced cell apoptosis via targeting SIRT6 (15). The cyclin-CDK complexes promotes cellular proteins phosphorylation, then drive the progress of cell cycle, which is essential in tumorigenesis (71).…”
Section: Mir-186 As a Tumor Suppressor Mirnamentioning
confidence: 99%
“…For instance, miR-125b inhibits the expression of MMP13 and suppresses CSCC cell proliferation, migration and invasion (11). miR-186 is an important member of cancer-associated miRs and has been reported to generally serve a tumour suppressive role in various types of human cancer, including chronic myeloid leukaemia (12), colorectal cancer (13), gastrointestinal stromal tumour (14), lung cancer (15), liver cancer (16), cervical cancer (17), and gastric cancer (18). miR-186 inhibits the proliferation, metastasis and epithelial-to-mesenchymal transition of colorectal cancer cells by targeting ZEB1 (13).…”
Section: Introductionmentioning
confidence: 99%